Study of Provision of Cellulose Nanocrystal Derived From Palm Oil Empty Fruits Bunches (EFB) - Marpongahtun; Aulia, Fenny; Gea, Saharman (Journal of Chemical Natural Resources, 2021)
Isolation and characterization of cellulose nanocrystal of alpha-cellulose from Empty Fruit Bunch (EFB) have been performed. Empty Fruit Bunch (EFB) was delignificated with 3.5% HNO3 and NaNO2, precipitated with17.5% NaOH, bleaching process with 10% H2O2. Nanocrystal was obtained through the hydrolysis of alpha-cellulose using 45% H2SO4. Nanocrystal surface structures cellulose was analyzed by Scanning Electron Microscopy (SEM) and the results show that the resulting cellulose Nanocrystal size was 79 nm. Analysis of thermal degradation using Thermal Gravimetric Analysis (TGA) shows that the cellulose nanocrystal was started at 160ÂºC decomposes. It shows the process of cellulose nanocrystal that isolated from alpha-cellulose has occurred.